Successful rapid return to performance following non-operative treatment of proximal hamstring tendon avulsion in elite athletes - Lauf, K.; van der Made, A. D.; Jaspers, R.; Tacken, R.; Maas, M.; Kerkhoffs, G. (BMJ Open Sport & Exercise Medicine, 2025)
Objectives Proximal hamstring tendon avulsion injuries are severe and potentially career-threatening for elite athletes. Until now, no data have been published on the non-operative treatment of this injury in elite athletes. Therefore, the objective of this case series was to describe return to performance in elite athletes after non-operative treatment of full-thickness proximal hamstring tendon avulsion injuries as well as provide detailed description of the rehabilitation process and provide a mechanobiological hypothesis on processes leading to successful outcomes.